Pertumbuhan Vegetatif Seedling Anggrek Dendrobium Woon Leng dengan Menggunakan Berbagai Media Tanam - Simamora, Rosanti Sari; Ganevianti, Dwi Wahyuni; Barchia, M. Faiz (Akta Agrosia, 2015)
Orchid plant is a plant that absorbs nutrients from the roots is relatively small for the needs of growing media utilization and nitrogen-producing plant species to optimize nutrient absorption. This study aimed to obtain the type of growing media and nitrogen -producing plant species that support the growth ofDendrobium seedlings Woon Leng. This research was conducted at the laboratory, Wire Agronomy, Faculty of Agriculture, University of Bengkulu using Divided Plots Experiment Design ( Split Plot Design ) two factors and four replications. The first factor giving the type of crops that control nitrogen (N0) Leucaena (N1), Wedelia trilobata (N2). The second factor giving the type of planting medium M1 : Charcoal, M2 : The roots of ferns, M3 : coconut fiber, M4 : Litter wood, M5 : Mixed Charcoal + fern roots, M6 : Mixed charcoal + coconut fiber, M7 : Mixed charcoal + wood litter, M8 : Mixed Roots fern + coconut fiber, M9 : Mixed Roots + Litter wood fern , M10 : A mixture of coconut fiber + wood litter. The results showed that administration of the M4 type of growing media (wood litter) M5 (a mixture of wood charcoal + fern root) and M8 (a mixture of coco + fern root) with the administration of nitrogen-producing plant specieslamtoro can improve the total plant weight gain. M1 planting medium (charcoal) with provision of nitrogen producing plant species can lamtoro increase in the number of leaves. Planting medium M4 (litter timber) and M9 medium (mixture of wood fern roots + litter) with wedelia treatment may increase in the number of leaves. Giving lamtoro nitrogen-producing plant species can increase the chlorophyll content of leaves , while the type of planting medium M4 (litter timber) and M9 (a mixture of wood fern roots + litter) gives in the number of leaf stomata.